2014
DOI: 10.1155/2014/842674
|View full text |Cite
|
Sign up to set email alerts
|

Foeniculum vulgareMill: A Review of Its Botany, Phytochemistry, Pharmacology, Contemporary Application, and Toxicology

Abstract: Foeniculum vulgare Mill commonly called fennel has been used in traditional medicine for a wide range of ailments related to digestive, endocrine, reproductive, and respiratory systems. Additionally, it is also used as a galactagogue agent for lactating mothers. The review aims to gather the fragmented information available in the literature regarding morphology, ethnomedicinal applications, phytochemistry, pharmacology, and toxicology of Foeniculum vulgare. It also compiles available scientific evidence for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
283
3
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(306 citation statements)
references
References 114 publications
4
283
3
16
Order By: Relevance
“…Different spices including sweet fennel are already well known for their disease healing capacity. Fennel seeds are recommended to reduce or cure many ailments such as abdominal pains, colic in children, constipation, diarrhea, flatulence, gastritis, irritable colon, and stomachache (12,22). In this study, we observed that sub-bactericidal concentrations of sweet fennel seed methanol extract and its major components could drastically inhibit CT production in different serogroups of V. cholerae.…”
Section: Discussionmentioning
confidence: 69%
“…Different spices including sweet fennel are already well known for their disease healing capacity. Fennel seeds are recommended to reduce or cure many ailments such as abdominal pains, colic in children, constipation, diarrhea, flatulence, gastritis, irritable colon, and stomachache (12,22). In this study, we observed that sub-bactericidal concentrations of sweet fennel seed methanol extract and its major components could drastically inhibit CT production in different serogroups of V. cholerae.…”
Section: Discussionmentioning
confidence: 69%
“…Stomach and intestinal problems, influenza, tranquilizer, insomnia, hypertension, fever Tranquilizer Sedative, anxiolytic activities [64], antibacterial, antifungal [65], vasorelaxant effect was evaluated in vitro in rat superior mesenteric artery rings [37] Matricaria chamomilla Tranquilizer and insomnia Tranquilizer…”
Section: Flatulencementioning
confidence: 99%
“…Depending on the variety it may be an annual, biennial or perennial herb. Survey of published literature revealed that significant research work have been carried out on various aspects of its cultivation (propagation), nutritive value, uses, phytochemistry and pharmacology of seeds and green herbs as well as toxicity of F. Vulgare [1]. Fennel has been known to controls many infectious disorders of microorganism origin [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Fennel has been known to controls many infectious disorders of microorganism origin [2][3][4][5]. Seeds and essential oil of fennel has been reported to possess antioxidant, antitumor, chemopreventive, cytoprotective, hepatoprotective, hypoglycemic, and oestrogenic activities [1]. In India fennel is cultivated in semi arid regions of Gujarat and Rajasthan states with an area of 760 lakh hectares and production of 129350 tonnes annually (Spice board, India).…”
Section: Introductionmentioning
confidence: 99%